SGR 0755-2933: A new high-mass X-ray binary with the wrong name - Doroshenko Victor; Santangelo Andrea; Tsygankov Sergey S.; Ji Long (EDP Sciences, 2022)
The soft gamma-ray repeater candidate SGR 0755-2933 was discovered in 2016 by Swift/BAT, which detected a short (∼30 ms), powerful burst typical of magnetars. To understand the nature of the source, we present here an analysis of follow-up observations of the tentative soft-X-ray counterpart of the source obtained with Swift/XRT, NuSTAR, and Chandra. From our analysis we conclude that, based on the observed counterpart position and properties, SGR 0755-2933 is not a soft gamma-ray repeater but rather a new high-mass X-ray binary. We suggest it be referred to as 2SXPS J075542.5-293353. We therefore conclude that the available data do not allow us to confirm existence and identify the true soft-X-ray counterpart to the burst event. The presence of a soft counterpart is nevertheless essential to unambiguously associate the burst with a magnetar flare, and we conclude that the magnetar origin of the burst and a precise burst location remain uncertain and require further investigation.